Revisiting the potential of community empowerment within UK neighbourhood policing meetings - Gasper, Roz (Policing and society, 2018)
Police attempts to engage with communities and involve the public in decision-making within co-governance meetings has a long history in the UK. This paper examines the most recent initiative for such engagement, exploring the potential and problems for community empowerment in meetings set up as part of the development of neighbourhood policing in the UK. The paper contributes to existing research by offering a more nuanced understanding of how co-governance is constructed in meetings, drawing on a longitudinal ethnography of the experience of these meetings in advantaged and disadvantaged communities. Our findings demonstrate the complex reality and practice of co-governance meetings between the police and community members and the paper explores three key themes in relation to these meetings. First, in examining the potential for community empowerment, we show that while these meetings may have some regressive effects, core attendees fully embrace them and seek to establish an active citizen identity. Secondly, we offer some support for a radical communitarian thesis, demonstrating how residents even in disadvantaged communities are able to have their voices heard. Finally, the research demonstrates that while the police attempt to control these meetings, this control is not uncontested with frequent challenges against police and partner (in)actions. The paper concludes by identifying critical areas of change for improving community empowerment in co-governance meetings with the police.